AN AUTOPSY BASED STUDY ABOUT BISEXUAL VARIATION IN THE FUSION OF STERNAL BODY SEGMENTS IN THE CENTRAL INDIA REGION (M.P.) (Journal of Forensic Medicine & Toxicology, 2018)
Age determination from unknown human skeletal remains or decomposed bodies is an important initial step in forensic investigation. Accurate determination of skeletal Age has been a critical issue in medico legal cases and the accuracy depends on the nature of material available and methods applied. Sternum is a bone which is easily retrievable even from the advance decomposed body and also from the bundle of bone so it become very important bone for age and sex determination in the advance stage of decomposition and from mutilated, fragmented bodies. In our study we have taken Total 770 subject in which 432 male and 338 female was taken between the age group of 10 to 70 years and data analysis was done by using SPSS software and relevant statistical test was applied. In our study bisexual variation in relation to fusion of sternal body segment was found inconclusive.
Keywords: Anthropometry; Bisexual variation; Age estimation; Sternum; body segment fusion